Building Social Construction and Tolerance In Customary Communication Law Communities (Study of Local Wisdom of Malay Tribes) - Marwan, Marwan; Alamsyah, Alamsyah (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to find the meaning and positive role of the culture of "Urang Kita" and Pi'il Pesenggiri among the Banjar and Lampung tribal communities and the Lampung community in building tolerant attitudes between groups and religious communities in Kuala Tungkal Jambo and Lampung. The next goal is to explore opportunities for the value of these traditions in building and affirming tolerant and moderate life in society Indonesia is plural today. This research was conducted using a descriptive qualitative approach using a review system that summarizes the results of primary research to present more comprehensive and balanced facts to find a description of a problem or topic under study. Data collection techniques are carried out by collecting various documents related to the focus of research. The data that has been collected is then studied in depth to find out reliable research results. Based on the discussion and analysis in several chapters above, the results of this study are concluded as follows: Tolerance is one of the important attitudes in forming a peaceful and serene life to build a just, prosperous, developed and prosperous society. Tolerance has been a culture of the Indonesian nation since time immemorial, and this attitude is increasingly needed and must be strengthened in the modern era when Indonesian society is more diverse and faces challenges from various ideologies and foreign cultures. One strategic and important approach in building tolerance and preventing divisive identity politics is through local wisdom, namely the values that live and are practiced by tribal communities in the archipelago, such as the Banjar community in Kuala Tungkal Jambi and the Lampung Pepadun community in Tulang Bawang Lampung. One of the traditions of local wisdom of the Banjar people in Kuala Tungkal Jambi refers to or greets other groups outside the Banjar tribe with the term "Urang Kita" or "Our Brothers". With this expression, the Banjar tribe calls or mentions and acknowledges the existence of other tribes, but they are still called as "Brothers". Other groups outside the Banjar tribe can be Malays, Bugis, Javanese, Batak, etc., both Muslim and non-Muslim. While the tradition of local wisdom of the Lampung tribe is in the values of life, especially "Pi'il Pesenggiri", which teaches to respect guests, protect and require honor as a condition for doing good. Committing bad or unethical acts is considered a violation of self-esteem or "pi'il", therefore guests or other groups should be protected or respected. Tolerant attitudes must continue to be built and strengthened as a basis for realizing a just, prosperous, prosperous country within the framework of the Unitary State of the Republic of Indonesia that is peaceful and upholds human values.